THE EDUCATIONAL GAME-BASED EMODUL: IS IT EFFECTIVE AND SOLUTION TO THE MERDEKA CURRICULUM? - Munir, Syahrul; Haryono , Agung; Rokhmani, Lisa; Inayati, Roufah; Anisya, Anisya; Masruro , Umi; Fitrianti, Wahyu (PT. BATARI EDU CALYA, 2023)
Various innovations in implementing learning activities are efforts to support the implementation of the Merdeka curriculum. One of the innovations was carried out by developing the Android-based